Uma análise pragmática do “Programa Pai Presente” do CNJ: convergência entre as teorias de Peirce e James sobre a lógica pragmática e a concepção de consequências práticas - Guimarães, Luize Êmile Cardoso (2015)
The present work is to study the philosophical pragmatism object with emphasis on theories of Peirce and James on the pragmatic approach and the design of practical consequences, in order to see how this philosophy of action may be useful to critically understand the law. In this sense, will be discuss the Peirce's theory of abduction as well as on the design of understanding of an object from its practical consequences observable in the light of Peirce's thought. Then we propose a counterpoint to the different way in which William James saw pragmatism, conceiving it as a method to become metaphysical disputes, making, therefore, use of aspects related to subjectivism and human psychologism. In this context, the central question of which part of this research is the following: It is pragmatically possible to work the theoretical categories of James and Peirce to think the PPP from their identities, despite the known differences between these? The provisional answer to this problem is yes because it takes into account the fact that the essence of pragmatism as a means to know something through its practical consequences is common to both authors and even if James has apparently radically detached from Peirce, you can find correspondences between the two theories. In order to give practical applicability to this study, testing his hypothesis from a specific case, we chose to do so, the "Pai Presente Program" (PPP), creating the internal affairs of the CNJ and whose main objective is to facilitate and stimulate the spontaneous recognition of paternity. PPP is composed of three provisionses: 12, 16 and 19 and in force since August 2010. This work will examine it under the pragmatic point of view, in order to search for their practical consequences from the figures provided by the CNJ until August 2012. the work of the structure is divided into five parts, namely: chapter 1 with introductory material about the whole theme addressed throughout the work, chapter 2 with the theoretical foundation, according to the theoretical framework above, chapter 3 with the presentation of the PPP, chapter 4 with the analysis of the relationship between the theory of Peirce and James and their applicability to the PPP, considering the numbers of the CNJ, and finally, chapter 5 with the final considerations presenting the confirmation of the hypothesis first proposed.